Karakterisasi dan Kinerja Membran Polyethersulfone Termodifikasi Aditif Anorganik secara Blending Polimer - Umi Fathanah; Hesti Meilina (Jurnal Serambi Engineering, 2021)
Recently, membrane technology has developed rapidly as a process for water treatment. The membrane process is in demand due to several advantages including being able to work at low temperatures, easier to operate and easy to scale up. Magnesium hydroxide (Mg(OH)2) is an inorganic compound that is inexpensive, non-toxic and hydrophilic, so it has the potential to be used as an additive in membrane fabrication. This study aims to determine the characteristics and performance (permeability and selectivity) of Polyethersulfone (PES) membrane modified with Mg(OH)2, using dimethyl Acetamide (DMAc) as solvent. The membrane was made by blending polymer with phase inversion technique and the characterization carried out included membrane morphological tests, functional group tests, water contact angle tests and evaluating membrane performance by measuring membrane selectivity and permeability. The results showed that the hydroxyl group contained in Mg(OH)2 was able to increase the hydrophilicity which was indicated by a decrease in the water contact angle on the modified membrane to 65o. The Mg(OH)2 additive acts as a pore-forming agent which can be seen in the changes in membrane morphology on the cross-section of the membrane surface. The performance of the membrane resulted in an increase in membrane permeability of 51 L/m2.hour.bar with humid acid rejection of 63%.